The Strengthening Position and Functions of Waqf on Nadzir as an Independent Institution - Faisal Faisal; Nursariani Simatupang (Jurnal Akta, 2022)
The purpose of writing in this study is to find out and analyze the position and function of nadzir Waqf as an independent institution so that it is expected to strengthen the role of nadzir Waqf in carrying out their duties, the approach used in this study uses normative juridical, the results of the research result state that Nadzir as the party who will determine the success of the Waqf implementation, only as an administrator who does not have more power, power and authority in managing the Waqf property that has been handed over to the Waqf. This is of course inseparable from the laws and regulations governing Nadzir Waqf itself as a guide in carrying out its activities, Nadzir Waqf in carrying out its duties and functions must pay attention to and be subject to various laws and regulations that are so many, many rules that must be obeyed by Nadzir made Nadzir inflexible in carrying out the development and management of the Waqf property.